Genetic variation of seven years old Araucaria cunninghamii progeny test in Bondowoso East Java. Issue 1 (July 2021) - Setiadi, D; Mashudi,; Hadiyan, Y; Susanto, M; Baskorowati, L; Pujiono, S; Adinugraha, H A; Sulaeman, M
Abstract: Araucaria cunninghamii is conifer trees with great commercial value for tropical and sub-tropical region. The genetic variation in growth i.e: height, diameter, volume was examined on 7 years old of A. cunninghamii progeny test at the area of Forest for Special Purpose (KHDTK) in Bondowoso, East Java. The progeny trial included 80 families from six provenances, with four replications and four trees in each row plots. The analysis showed that there were great variations of genetic growth within provenances and between provenances. It was discovered that A. cunninghamii from Fak-fak Papua had the best height growth (mean height= 10.65 m with volume mean annual increments =8.39 m 3 ha-1 year-1), while A. cunninghamii from Serui Papua had the best diameter growth (mean diameter =15.84 cm). The individual heritability for height and diameter were classified as moderate (h 2 i = 0.16; 0.30). The genetic correlation between the height and diameter was quite strong (r g = 0.79). As a result of the findings, the future genetic program strategy in the research will focus on increasing genetic biodiversity for the species in order to increase Mean Annual Increment (MAI) for supplying Indonesia's wood demand.. The genetic diversity will be achieved through some steps in the strategy i.e: best genetic growth selection within provenances; combining of genetic of the best growth between provenances; and establishment of the progeny trial for next generations.